Silicon doped by molecular doping technique: Role of the surface layers of doped Si on the electrical characteristics. (February 2016) - Caccamo, Sebastiano; Puglisi, Rosaria A.; Di Franco, Salvatore; D'Urso, Luisa; Indelicato, Valeria; Italia, Markus; Pannitteri, Salvatore; La Magna, Antonino
Abstract: We present results on an investigation about the chemical–physical properties of the Si surface after molecular doping (MD) method and successive annealing. The purpose of this work is to study the atomic structure of the first layers of silicon after the doping procedure in order to evaluate the possible intermixing between the carbon atoms constituting the precursor molecule and the Si atoms of the substrate. Moreover the role of this intermixed layer on the electrical characteristics of the semiconductor is also examined. The chemical characteristics of the samples after the doping procedure are obtained by performing X-ray spectroscopy, while the electrical characteristics are studied by four probe point and spreading resistance profiling. In order to clean the Si from the presence of the surface intermixed layer a wet chemical etch based on HNO3 is proposed. Four probe point measurements have been performed also after the etching to demonstrate that it is possible to modulate the sample sheet resistance as a function of the post-doping chemical treatment of the surface.